Data Power in Action Urban Data Politics in Times of Crisis - Söderström, Ola; Datta, Ayona (Bristol University Press, 2024)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Today, the intensive use of data is changing politics, power relations and everyday life. Drawing on the study of different cities in the Global South, this book explores how data have become a generative force in shaping what cities are, how they are governed and inhabited, especially during times of crisis, such as the COVID-19 pandemic.